ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN PADA PENDAPATAN ASLI DAERAH (PAD) ATAS PAJAK REKLAME DI DINAS PENDAPATAN DAERAH KOTA BATAM - Suriyatni, Imelda; Putra, Rizky Eka; Hati, Ravika Permata (Universitas Riau Kepulauan, 2016)
Research on the Application of Analysis to the Government Accounting Standards Revenue Office by the Regulation Governing Batam (PP) No.71 of 2010 on Government Accounting Standard Batam City Government (Revenue Service case study in Batam) aims to determine the advertisement tax revenue summary report and the financial statements in Batam City Revenue Service compliance in the implementation of Government Regulation No. 71 of 2010 which is the Government AccountingStandards. This research uses descriptive method is to describe the data obtained from the various agencies that support the theory. The result also showed that pemaparandata of the agency in accordance with Government Accounting Standards contained in Government Regulation No 71 of 2010 of the Government Accounting Standaerd revenue Service for use in Batam Keywords: Implementation of the Government Accounting Standards Board, Advertisement Tax.